1988
DOI: 10.1007/bf01091716
|View full text |Cite
|
Sign up to set email alerts
|

Sugars of the unfermented sap and the wine from the oil palm,Elaeis guinensis, tree

Abstract: The sugar composition of the unfermented sap from oil palm (Elaeis guinensis) trees growing in the plantations of the Nigerian Institute for Oil Palm Research, Benin City, has been determined. While sucrose concentration ranges from 9.59 to 10.59% (w/v) in the pure unfermented sap, that of either glucose or fructose is much less than 1% (w/v) (0.13-0.73% w/v). Raffinose occurs in traces only (0.13-0.35 w/v). These results were derived from our improved methods which eliminate completely, or reduce to a bare mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 3 publications
2
33
0
Order By: Relevance
“…Chooklin et al (2011) reported the total sugars for oil palm sap were 19.17 g/L or 1.92% (w/v) and comprised only glucose (1.66%) and fructose (0.26%). In a separate study, saps from oil palm trunk were reported to have 11% total sugars (Eze and Ogan 1988). Goh et al (2013) reported sawdust extracted from oil palm and coconut trunks contained approximately 2.77% and 21.2% w/w total sugars, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Chooklin et al (2011) reported the total sugars for oil palm sap were 19.17 g/L or 1.92% (w/v) and comprised only glucose (1.66%) and fructose (0.26%). In a separate study, saps from oil palm trunk were reported to have 11% total sugars (Eze and Ogan 1988). Goh et al (2013) reported sawdust extracted from oil palm and coconut trunks contained approximately 2.77% and 21.2% w/w total sugars, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Aliquots were applied to cellulose TLC plates and developed in a solvent mixture of isopropyl alcohol/pyridine/water/acetic acid (8:8:4:1 by volume) (Matsui 1970). The plates were air dried and spots were visualized by spraying the plate with a solution containing aniline (1 mL), diphenylamine (1 g in 10 mL distilled water), and phosphoric acid (100 ml) (Eze and Ogan 1988). The plates were heated at 120°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…It should be noticed that the oil palm (Elaeis guinensis) also contains around 10% sucrose 12 and thus can be considered as a source of fermentable sugar.…”
Section: Sugar Palmsmentioning
confidence: 99%